2020
DOI: 10.1002/cjce.23881
|View full text |Cite
|
Sign up to set email alerts
|

Response surface modelling of CO2 capture by ammonia aqueous solution in a microchannel

Abstract: Post-combustion CO 2 capture is one strategy of greenhouse gases mitigation. Ammonia is a useful option as CO 2 absorbent and an alternative to conventional amine-based solutions. This study deals with CO 2 capture by ammonia aqueous solution in a co-current two-phase flow by utilizing a T-shaped microchannel. Three parameters of temperature, gas flow rate, and ammonia concentration were considered as the main parameters affecting the CO 2 capture efficiency. A response surface methodology based on central com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The internal studentized residuals and predicted values for the % of MB dye removal are correlated in Figure c. The randomly distributed plot demonstrated that for all of the obtained responses, the variance of originally collected data remains the same . Internally studentized residuals and run numbers for the % removal of MB dye were correlated and are shown in Figure d.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…The internal studentized residuals and predicted values for the % of MB dye removal are correlated in Figure c. The randomly distributed plot demonstrated that for all of the obtained responses, the variance of originally collected data remains the same . Internally studentized residuals and run numbers for the % removal of MB dye were correlated and are shown in Figure d.…”
Section: Resultsmentioning
confidence: 82%
“…The internal studentized residuals and predicted values for the % of MB dye removal are correlated in Figure 7 c. The randomly distributed plot demonstrated that for all of the obtained responses, the variance of originally collected data remains the same. 59 Internally studentized residuals and run numbers for the % removal of MB dye were correlated and are shown in Figure 7 d. This plot revealed that there was no valid correlation between experimental data points and the outcomes observed. Design Expert software generated multiple runs for various independent variables.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation